Through‐the‐scope esophageal stent for the relief of malignant dysphagia: Results of a multicentric study (with video). Issue 1 (3rd June 2020) - Mangiavillano, Benedetto; Auriemma, Francesco; Bianchetti, Mario; Mantovani, Nicola; Pilati, Stefano; Reggio, Dario; Barletti, Claudio; Forcignanò, Edoardo; Pentassuglia, Giuseppe; Arezzo, Alberto; Cavargini, Elena; Fabbri, Carlo; et al.
Abstract : Background and aim: In presence of malignant dysphagia, in patients unfit for surgery, the placement of a self‐expandable metal stent (SEMS) represents a safe and effective palliative treatment. Esophageal stents (ES) present an over‐the‐wire mechanism where the stent is deployed under X‐ray control. Recently a through‐the‐scope (TTS) ES was launched. The aim of our retrospective study is to assess the technical and clinical success of the new TTS‐ES. Materials and methods: Patients with malignant dysphagia caused by esophageal cancer or ab‐extrinsic compression, who underwent TTS esophageal stent in six Italian endoscopic referral centers, were retrospectively reviewed. Results: A total of 40 patients were enrolled. TTS stent placement was successful in 39/40 patients (97.5%). 31 patients had an Ogilvie score of 4, nine an Ogilvie 3. After 2 weeks from stent placement 29 reported Ogilvie score of 0, eight a score of 1. None of the patients developed retrosternal pain requiring drugs. No patient experienced perforation, bleeding or migration. A total of seven patients (18%) developed dysphagia as late adverse event (AE). Conclusion: Through‐the‐scope ES presented less AEs, in terms of bleeding and perforation, if compared to the previous published data. An anti‐migration system could be helpful, especially when the stent is placed for "ab‐extrinseco" malignant dysphagia.